Paths of an eighteenth-century manuscript: from Vila Real de Sabará to contemporaneity (Filologia e Linguística Portuguesa, 2020)
The path followed by a manuscript from its production to the contemporaneity, can indicate marks of political actions that decided for its preservation. In order to illustrate this assumption, we present the Royal Charter to the Chamber Judge and officials for the contribution of the voluntary subsidy of 1755 and more specifically its copy, from 1777. From the codicological analysis of the manuscript, it is posible to observe, since its production, its longevity and the safety with its circulation. The catalog "Alberto Lamego’s Collection", by IEB - Instituto de Estudos Brasileiros - is a fundamental instrument for the analysis of the manuscript’s transmission phases as it indicates places of landings in archives where efforts are also evidenced for its preservation and dissemination. Paleographic and diplomatic studies provide information that allows us to deduct its authorship from the text and testimony, date and certain individual formulas of these documentary species, making it possible to verify its authenticity and genuineness. All those are essential characteristics for the semidiplomatic edition can be used as a safe documentary source for future research. Collectors, archivists, philologists and other researchers are co-authors in this important task of transmitting documents to future generations.